Baksos Sirkum Massal dan Pemeriksaan Kesehatan bagi Masyarakat di Yayasan As-Sunah Makassar - Dewi, Resky Karnita; Zamli (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This activity aims to provide free health services to children, particularly through mass circumcision and health check-ups, and to strengthen collaboration between the academic community and society. This community service activity was carried out through several structured stages to ensure the smoothness and benefits of the activity for the community. The results of this community service activity showed a positive impact on the community at the As-Sunah Makassar Foundation. This activity also increased public knowledge about the importance of maintaining health, both through counseling and direct interaction with health workers. This activity not only provides direct benefits in the form of health services but also increases public knowledge and awareness of the importance of maintaining cleanliness and health in general.